2016
DOI: 10.1371/journal.pone.0147622
|View full text |Cite
|
Sign up to set email alerts
|

Soft and Hard Textured Wheat Differ in Starch Properties as Indicated by Trimodal Distribution, Morphology, Thermal and Crystalline Properties

Abstract: Starch and proteins are major components in the wheat endosperm that affect its end product quality. Between the two textural classes of wheat i.e. hard and soft, starch granules are loosely bound with the lipids and proteins in soft wheat due to higher expression of interfering grain softness proteins. It might have impact on starch granules properties. In this work for the first time the physiochemical and structural properties of different sized starch granules (A-, B- and C-granules) were studied to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…This agrees with previous results provided by Zhu et al Minor peaks were also observed at 2 θ ≈ 20° and 27°. The peak observed at 2 θ ≈ 20° indicates the presence of some V‐type starch crystals in rice varieties, which may indicate starch complexes containing lipids and proteins . The residual fractions (1 and 2) and black rice starch in our systems had similar crystallinity (≈22%), with no significant differences ( p > 0.05) between the samples.…”
Section: Resultsmentioning
confidence: 61%
“…This agrees with previous results provided by Zhu et al Minor peaks were also observed at 2 θ ≈ 20° and 27°. The peak observed at 2 θ ≈ 20° indicates the presence of some V‐type starch crystals in rice varieties, which may indicate starch complexes containing lipids and proteins . The residual fractions (1 and 2) and black rice starch in our systems had similar crystallinity (≈22%), with no significant differences ( p > 0.05) between the samples.…”
Section: Resultsmentioning
confidence: 61%
“…This result is predicted by the work of Eliasson and Larsson (1983) , Ao and Jane (2007) , and Wei et al (2010) who showed that the gelatinization enthalpy of wheat starch is independent of the granule size distribution. However, others have found higher gelatinization enthalpies for A-type than for B-type starch granules in wheat ( Chiotelli and Le Meste, 2002 ; Li et al , 2013 ; Kumar et al , 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…Approximately 30% of the wheat starch granules were spherical, medium-sized (3–10 μm), while 10% were really small grains (under 3 μm) with irregular forms (as it can be seen in Figure 2 a). The heterogeneity of the wheat flour starch granules could be attributed to the wheat variety (soft or hard wheat), the amylose content, and especially the moment in which is formed during anthesis or their different times of formation during grain development [ 34 , 35 , 36 , 37 , 38 ]. There are also many studies that confirm the presence of amylose in the peripheral region of the starch granules as it was likewise assessed in our study.…”
Section: Resultsmentioning
confidence: 99%